Towards freedom in South Asia : democratization, peace, and regional cooperation - Pai Panandiker, V. A., 1935-; Tripathi, Rahul; International Centre, Goa.; South Asia Together Project (New Delhi : Konark Publishers, 2008)
Contributed articles prepared for the plenary conference under the South Asia Together Project of International Centre, Goa.
"Under the auspices of the International Centre, Goa."
Includes bibliographical references and index.
Keywords: Democratization -- South Asia -- Congresses; Democracy -- South Asia -- Congresses; Peace-building -- South Asia -- Congresses; South Asia -- Politics and government -- 21st century -- Congresses